Zespół Cushinga wywołany długotrwałym stosowaniem kortykosteroidów w leczeniu atopowego zapalenia skóry - Akkuş, Yasin; Baş, Veysel N.; Yılmaz, Zülal (Pediatric Endocrinology Diabetes and Metabolism, 2020)
Corticosteroid-containing creams, pomades and ointments are frequently prescribed for the treatment of atopic dermatitis by allergologists and immunologists, dermatologists and many other physicians. This case is about a 1-month old infant who acquired iatrogenic Cushing syndrome after being applied diflucortolone valerate, a strong corticosteroid, ointment 3 to 4 times a day over the course of 4 months after being prescribed by a primary care physician.